Training in diabetes education: meanings attributed by primary care nurses - Magda Coeli Vitorino Sales Coêlho; Camila Aparecida Pinheiro Landim Almeida; Ana Roberta Vilarouca da Silva; Luana Kelle Batista Moura; Lucíola Galvão Gondim Corrêa Feitosa; Laura Barbosa Nunes
ABSTRACT Objective: seize meanings attributed by primary care nurses to training in diabetes education. Method: exploratory and descriptive study, with a qualitative approach, with twenty primary care nurses; semistructured interview script, with interviews processed in the IRaMuTeQ software and analyzed through the Descending Hierarchical Classification. The results were subsidized in the Representational Theory of Meaning. Results: nurse training in diabetes education is insufficient for holistic action, although it allows the community to be instrumentalized in specific issues about the disease, using the limited tools available, especially lectures. Nurses find themselves in a context of challenges, improvisations, weaknesses, and limitations that determine the meaning attributed to diabetes education and subsequent actions. Conclusion: the meanings attributed by the nurses revealed an incipient training, which limits the quality of care provided and instigates the search for qualification.